2019
DOI: 10.1038/s41598-019-42539-6
|View full text |Cite
|
Sign up to set email alerts
|

The left-cradling bias and its relationship with empathy and depression

Abstract: Women usually cradle their infants to the left of their body midline. Research showed that the left cradling could be altered by affective symptoms in mothers, so that right cradling might be associated with a reduced ability to become emotionally involved with the infant. In this study, we assessed cradling-side bias (using family photo inspection and an imagination task), as well as depression and empathy, in 50 healthy mothers of 0–3 years old children. The main finding was that the strength of the left-cra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 76 publications
2
30
0
Order By: Relevance
“…These studies indicated that autistic symptoms involve not only social communication and repetitive behaviors, but also influence to some extent motor capacities and the regulation of attention and emotion (59). Analogously, previous findings seem to endorse the opinion that empathy (37,38), social attachment (35,39), and emotion lateralization (13,14) strongly affect early lateral cradling preferences in females. Moreover, a recent study conducted by Forrester and colleagues (60) suggested interesting associations between left-cradling bias and enhanced social processing abilities in (typically developing) 5-6 years old children.…”
Section: Introductionsupporting
confidence: 54%
See 3 more Smart Citations
“…These studies indicated that autistic symptoms involve not only social communication and repetitive behaviors, but also influence to some extent motor capacities and the regulation of attention and emotion (59). Analogously, previous findings seem to endorse the opinion that empathy (37,38), social attachment (35,39), and emotion lateralization (13,14) strongly affect early lateral cradling preferences in females. Moreover, a recent study conducted by Forrester and colleagues (60) suggested interesting associations between left-cradling bias and enhanced social processing abilities in (typically developing) 5-6 years old children.…”
Section: Introductionsupporting
confidence: 54%
“…No difference was found in lateral cradling preferences between the mothers of typical and autistic children in the first three months after delivery, that is the period in which leftcradling bias is particularly strong in healthy mothers (3,4,10) but not in mothers with affective symptoms such as stress, anxiety or depression (38,62,63). The left-cradling bias was clearly apparent from photos of the first age group (0-3 months) in both groups: significantly in typical children and trending towards significance in ASD children (probably due to the smaller sample size).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…It should be pointed out that, in the vast literature on cradling behavior focusing on the relationship between lateral cradling preferences and attachment styles, this is the first report to exploit ad hoc instruments for evaluating the latter. There is convincing evidence supporting the link between cradling asymmetries and various instances of emotional and affective behaviors, such as the establishment of an emotional bond between the cradling and cradled individuals, the interpretation of emotional signals of well-being in children, and the presence of affective symptoms such as depression and anxiety in mothers (Malatesta, Marzoli, Rapino, & Tommasi, 2019;Scola, Arciszewski, Measelle, & Vauclair, 2013;Sieratzki & Woll, 2002;Weatherill et al, 2004). Likewise, there is compelling evidence that positive attachment styles are related positively to optimal caregiving behaviors, organized maternal responsiveness to the emotional states of the child and greater parental investment, as well as negatively to mother's affective mental states, such as depression and anxiety (Belsky et al, 1991;Bifulco, Moran, Ball, & Lillie, 2002;Del Giudice, 2009;Marazziti et al, 2007;Seifer et al, 1996).…”
Section: Doll Position Left Midline Right Left Versus Rightmentioning
confidence: 99%